PERMANENT REVOLUTION AND PERPETUAL PEACE: Revisiting Kantian Cosmopolitanism - Palatty, Roy Varghese (Journal of Dharma, 2010)
We live in a globalized cosmopolitan world. Solitary conception of one’s existence is not only limited in its existential boundaries they set up, but it is dangerous to the humanity as a whole. Kantian theory of cosmopolitan right is considered as one of the most important philosophical origins of modern cosmopolitan thought. He did not, of course, invent either the idea or the name of cosmopolitanism, which he drew from the ancient Stoics and rediscovered in the interstices of modern revolutionary movements. But his great achievement was to transform it into a philosophical principle of the modern age based on the notion that nationalism was a sign of human immaturity and enslavement to the passions and that ‘genuine principle of right’ necessarily points toward a ‘universal law of humanity,’ which would transcend the nation-state. As Hannah Arendt rightly commented, one becomes a member in the world community by the fact of being human - one’s "cosmopolitan existence." Each human being dwells in two communities: one, the local community by birth and second, the community of human argument and aspiration. While answering the question on nature’s ‘final design,’ Kant, in no means unequivocal, argues that it is nothing but "a cosmopolitan whole." However, cosmopolitan right is also seen as a banner or label under which powerful nations conduct wars against their enemies and portray them as enemies of humanity itself. Carl Schmitt, who subscribes to such a view, believed that the moralization of war under a cosmopolitan flag has a close affinity to the totalization of war, since it turns the enemy into an ‘inhuman monster’ who ‘must be definitely annihilated.’ In the same way, Hegel makes critique on Kant’s theory of cosmopolitan right on the ground of its ‘fixed conception’ as regressive and non-nationalistic, where all the particularities of the nation-states are subsumed and eliminated. It seems however, Hegel’s attempt was not abolishing Kant’s cosmopolitan theory, but rather advancing Kantian framework beyond the formal natural law. Kant’s theory of a cosmopolitan order was not merely an idealistic irrelevance to the realist play of power politics, nor was it a moral trap or an exercise in self-delusion. It was rather a philosophical expression of a determination to resist the pressures of nationalism, overcome the external violence of modern state, and turn the idea of universality into a concrete reality. Cosmopolitanism as Kant proposed is to be defended against ‘spiritless radicalism,’ as Arendt aptly called it, albeit on the understanding that Schmitt’s destructive criticism is justifiable inasmuch as it captures ‘what is’ from the standpoint of power politics. As Kant rightly says, "political moralists" can always produce the contrary by fashioning morality to suit his own advantage as a statesman.